Antitumor Activity of Pt(II), Ru(III) and Cu(II) Complexes - Gałczyńska, Katarzyna (Molecules, 2020)
Metal complexes are currently potential therapeutic compounds. The acquisition of resistance by cancer cells or the effective elimination of cancer-affected cells necessitates a constant search for chemical compounds with specific biological activities. One alternative option is the transition metal complexes having potential as antitumor agents. Here, we present the current knowledge about the application of transition metal complexes bearing nickel(II), cobalt(II), copper(II), ruthenium(III), and ruthenium(IV). The cytotoxic properties of the above complexes causing apoptosis, autophagy, DNA damage, and cell cycle inhibition are described in this review.